Comparison of Resorption in Autogenous Dorsal Onlay Cartilage Grafts: An Experimental Study - Öner, Fatih; Kozan, Günay (Springer Science and Business Media LLC, 2024)
Abstract Objectives The present study was designed to compare the graft resorption characteristics of autogenous cartilage from the septum, auricle, and costal in the superficial muscular aponeurotic system of the nasal dorsum of the rabbit model. Methods Equal-sized perichondrium-free septal, auricular, and costal cartilage grafts were collected from fifteen New Zealand white rabbits. Cartilage grafts were taken at the scale of two grafts from each animal’s ear, two from its costal part, and one from its septum. Costal cartilage grafts that were shaped with a micro-motor device and monopolar electrocautery, elastic cartilage grafts that were shaped with a micro-motor device and monopolar electrocautery, and septal cartilage grafts that were shaped with a scalpel were all implanted into the dorsum of rabbit’s noses to create five groups. All autogenous cartilage tissues were removed 3 months later. Cartilages were evaluated for histological features, graft mass, and chondrocyte density resorption. Results The elastic cartilage group, where electrocautery was used to shape the cartilage, had a higher resorption score than the other groups. The costal cartilage graft shaped with a micro-motor was also observed to have the best cartilage regeneration score. Conclusion We observed that the resorption of costal cartilage was lower than that of ear and septum cartilage. It was determined that micro-motor application for the shaping process caused less resorption and stimulated more regeneration than cautery application. Level of Evidence III This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266.
Keywords: Costal Cartilage; Rabbit model; Animals; Autogenous cartilage; Original Articles; Rabbits; Ear Cartilage; Rhinoplasty; Transplantation, Autologous; Cartilage resorption; Nasal Septum